Skrining Hipotiroid Kongenital (SHK) Pada Ibu Hamil di Puskesmas Tajurhalang Kabupaten Bogor - Munir, Rindasari; Kusmiati, Meti; Fauziah, Nurul Azmi; Ningrum, Anggun Setia (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
According to WHO, in several developed countries such as America, Japan, Australia and Europe, since 197-, neonatal screening programs for hypothyroidism have been implemented so as to reduce the occurrence of mental retardation in children (Apriliani et al., 2021). Symptoms of hypothyroidism in newborns are usually not very obvious and congenital hypothyroidism can cause severe mental retardation unless therapy is received early, so a congenital hypothyroid (HK) screening examination is very important to do(Apriliani et al., 2021). Congenital Hypothyroidism Screening is effective 48-72 hours after birth(Ida Bagus Eka Utama Wija, 2020). Based on the pre and post test scores from 30 participants, it was found that there was an increase in the good category in knowledge with an average score of 1.7 to 3.00, meaning that the counseling was successfully implemented.There needs to be awareness of pregnant women, where the task of building awareness is held by health workers, so it is hoped that health agencies which are already required to run the SHK program will be more aggressive and package their invitations to pregnant women well.